Influence balneotherapy on spa Truskavets’ with taking Canephron® N on urina lithogenicity and its metabolic and neuroendocrine-immune accompaniments in patients with chronic pyelonephrite and cholecystite - Shulyak, Oleksandr V.; Flyunt, Igor-Severyn S.; Flyunt, Victor R.; Fil’, Vitaliǐ M.; Hrinchenko, Borys V.; Snihur, Oleh V.; Zukow, Walery; Yanchiy, Oksana R.; Popovych, Igor L. (Journal of Education, Health and Sport, 2015)
Shulyak Oleksandr V., Flyunt Igor-Severyn S., Flyunt Victor R., Fil’ Vitaliǐ M., Hrinchenko Borys V., Snihur Oleh V., Zukow Walery, Yanchiy Oksana R., Popovych Igor L. Influence balneotherapy on spa Truskavets’ with taking Canephron® N on urina lithogenicity and its metabolic and neuroendocrine-immune accompaniments in patients with chronic pyelonephrite and cholecystite. Journal of Education, Health and Sport. 2015;5(11):453-465. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.34351 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A453-465 https://pbn.nauka.gov.pl/works/673673 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.09.2015. Revised 25.10.2015. Accepted: 24.11.2015. INFLUENCE BALNEOTHERAPY ON SPA TRUSKAVETS’ WITH TAKING CANEPHRON® N ON URINA LITHOGENICITY AND ITS METABOLIC AND NEUROENDOCRINE-IMMUNE ACCOMPANIMENTS IN PATIENTS WITH CHRONIC PYELONEPHRITE AND CHOLECYSTITE Oleksandr V. Shulyak1, Igor-Severyn S. Flyunt2, Victor R. Flyunt3,6, Vitaliǐ M. Fil’2, Borys V. Hrinchenko3, Oleh V. Snihur3, Walery Zukow4, Oksana R. Yanchiy5, Igor L. Popovych6 1Scientic Reseach Institute of Urology, Kyiv, Ukraine Avshulyak@yandex.ua 2Faculties of Biology and Physical Education, Ivan Franko Pedagogical University, Drohobych, Ukraine iflyunt@bk.ru fillvitalij@rambler.ru 3JSC “Dnipro-Beskyd”, Truskavets’, Ukraine t.verdo@mail.ru 4Faculty of Physical Education, Health and Tourism, Kazimierz Wielki University, Bydgoszcz, Poland w.zukow@ukw.edu.pl 5Departament of Biology, OO Bohomolets’ National Medical University, Kyiv, Ukraine 6Laboratory of Balneology, OO Bohomolets’ Institute of Physiology NAS, Truskavets’-Kyiv, Ukraine i.popovych@biph.kiev.ua SUMMARY Objective. We know that balneotherapy on spa Truskavets' did not significantly affect the parameters of urina Lithogenicity, including Ca/Mg ratio, so search for means of reducing urina Lithogenicity remains relevant. We also know that Phytopreparation Canephron® N recommended for inclusion in complex therapy of chronic pyelonephrite as effective elimination of infectious kidney inflammation, prevention of recurrence of inflammation and lithogenese. Aim: to find out the possibility of reducing urina Lithogenicity influenced balneotherapy on spa Truskavets' by additional taking Canephron® N. Results. Standardized balneotherapy not significantly affect urina Lithogenicity in patients with chronic pyelonephrite and cholecystite, even showed a trend to increase, while additional use Canephron® N significantly reduces urina Lithogenicity by reducing the concentration of Uric acid and downward trend Calcium. Reducing urina Lithogenicity accompanied by a decrease urina concentration Chloride and Potassium, and Baevskiy’s Activity Regulatory Systems Index, Asymmetry δ-, θ- and α-rhythms of background EEG and α-rhythm normalized Power Spectrum Density (PSD) in right loci Fp2, F8, T6 and O2, while HRV markers of vagal tone (RMSSD, pNN50, TI) also Frequency Deviation θ- and β-rhythms, Amplitude β- and δ-rhythms, δ-rhythm PSD in loci Fp2, F8, T3, T5, O1, O2, β-rhythm PSD in loci Fp1, F4 and θ-rhythm PSD in loci T3 and F7 rising. However, Canephron® N preventes or reverses increasing Uric acid plasma level, Mineralocorticoide Activity, Sympathetic tone, Baevskiy’s Stress Index and PSD ULF HRV also decreasing PSD VLF HRV. Concerning parameters of Immunity Canephron® N decreases blood level active T-Lymphocytes but increases level B-Lymphocytes, Stubnucleary Neutrophiles and total Leukocytes also prevents or reverses increasing CD16+ NK-Lymphocytes, CD8+ and Theophilinesensitive T-Lymphocytes, Monocytes and serum IgM also decreasing CD4+ T-Lymphocytes and Neutrophiles Phagocytose Count vs Staphylococcus aureus. In addition, Canephron® N potentiates increasing Parathyrine Activity, serum level IgG and Bactericidic Capacity of Neutrophiles vs Staphylococcus aureus also decreasing Urea and Creatinine plasma level, Sodium urina concentration and Neutrophiles Phagocytose Count vs Escherichia coli. Conclusion. Introduce Canephron® N into standard balneotherapeutic complex spa Truskavets’ contribute to decrease urina Lithogenicity accompanied by decreasing of HRV and EEG markers of chronic Stress and favorable modulation parameters of Immunity in patients with chronic pyelonephrite and cholecystite. Keywords: lithogenicity of urina, EEG, HRV, immunity, spa Truskavets’, Canephron® N.